2016
DOI: 10.1155/2016/3018135
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Hepatitis C Serological Status with Several Risk Factors in Indonesia

Abstract: Hepatitis is an inflammation of the liver commonly caused by viral infection such as hepatitis A, B, C, D, and E but it is also possible by other causes. Infection with hepatitis C virus is also referred to as a disguise because the early infection is often asymptomatic that often goes undetected. This study aims at determining the several associated risk factors with hepatitis C serological status. The study design is cross-sectional. The biomedical data collection was carried out in 33 provinces in Indonesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
2
0
1
Order By: Relevance
“…Such practices are the reason for the association of exposure to therapeutic injections and hepatitis. We report dental checkup as a strong predictor of HCV infection (OR = 11.59, 95% CI 3.35-40.098) which is aligning with the reporting of Pracoyo et al (OR = 2.26, 95% CI 0.98-5.2)[34]. This could be resulted due to the use of unsterilized dental equipment.…”
supporting
confidence: 90%
“…Such practices are the reason for the association of exposure to therapeutic injections and hepatitis. We report dental checkup as a strong predictor of HCV infection (OR = 11.59, 95% CI 3.35-40.098) which is aligning with the reporting of Pracoyo et al (OR = 2.26, 95% CI 0.98-5.2)[34]. This could be resulted due to the use of unsterilized dental equipment.…”
supporting
confidence: 90%
“…A strict screening test before transfusion has accounted for a lower risk of pathogen transmission through blood unit (<1 case per 1 million blood unit) in high-income countries [ 2 ]. A previous study in Indonesia evaluated the association between blood transfusion and hepatitis C seropositivity in a large population derived from the Indonesian Basic Health Research and found that this association was not significant statistically [ 30 ]. In addition, the widespread use of erythropoietin to treat anemia in chronic kidney disease contributes to fewer transfusion practice and, consequently, decreased risk of HCV transmission [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its low prevalence, HCV seropositivity remains a healthcare concern as no vaccine is yet available; and without active screening surveillance the infected are usually diagnosed at a later stage with cirrhosis or liver cancer. In Indonesia, to our knowledge, only one study on HCV seroprevalence was perform in healthy subjects, where 2.2% were found to be HCV positive 6 ; while HBsAg prevalence was found to be 1.1% in young adults of Singapore 7 .…”
Section: * Corresponding Authormentioning
confidence: 92%